2009
DOI: 10.1590/s1415-790x2009000300005
|View full text |Cite
|
Sign up to set email alerts
|

Mapping malaria risk using environmental and anthropic variables

Abstract: Despite much research in the identification of areas with malaria, it is urgent to further investigate mapping techniques to achieve better approaches in strategies to prevent, mitigate, and eradicate the mosquito and the illness eventually. By using spatial distributed modeling techniques with Geographical Information Systems (GIS), the study proposes methodology to map malaria risk zoning for the municipality of Buenaventura in Colombia. The model proposed by Craig et al.¹ using climatic information was adap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
0
4
0
1
Order By: Relevance
“…Several methods have been used to map malaria risk. GIS-based spatial modeling techniques were adopted by Rincón-Romero and Londoño for malaria risk mapping in Columbia and by Ferrao et al in Mozambique [14,15]. Others promote spatial statistical approaches to map malaria risk.…”
Section: Introductionmentioning
confidence: 99%
“…Several methods have been used to map malaria risk. GIS-based spatial modeling techniques were adopted by Rincón-Romero and Londoño for malaria risk mapping in Columbia and by Ferrao et al in Mozambique [14,15]. Others promote spatial statistical approaches to map malaria risk.…”
Section: Introductionmentioning
confidence: 99%
“…In Latin America, few studies have attempted to categorise and map malaria risk. One of them used environmental and anthropic variables to design a malaria risk map for Buenaventura municipality in the Colombian Pacific region and showed that 89% of the cases corresponded to areas with moderate/high malaria risk [25]. Later, risk maps for Colombia and surrounding areas [26], and for northern South America [22] were produced based on expert opinion of key environmental and population risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…Two of them focused on the effects of climatic change associated with El Niño/Southern Oscillation‐ENSO on the number of malaria cases . Another study that mapped malaria risk for the Pacific Coast municipality of Buenaventura and showed a 78.8% reduction in areas under malaria risk when environmental and anthropic variables were included in the model . In addition, a high spatial resolution (90 × 90 m) malaria risk map for Colombia, based on environmental and human population data, helped to demonstrate the relationship between mean risk scores with total cases by the municipality, and provided an accurate spatial representation of risk potential to vector exposure .…”
Section: Introductionmentioning
confidence: 99%